In Vitro And Theoretical DNA Interaction Study of Zinc Complexes (Global Journal of Sciences, 2025)
In this work, we undertake a tentative analysis into the multi-layered realm of zinc complex DNA interactions, integrating empirical in vitro findings with cutting-edge theoretical modelling. The focus of our study involves the synthesis and thorough characterization of the Zn(DIP)2(DMP)2·2H2O complex, with the aim of establishing a fundamental comprehension of its structural attributes. The inquiry is built upon the structural foundation provided by analytical techniques such as UV-visible and IR spectroscopy, as well as 1H NMR data. In the molecular framework presented, we systematically investigate the principles of binding, thermodynamics, and kinetics that govern the dynamic interactions between zinc complexes and DNA. The progression of our exploration is characterized by a comprehensive examination of several spectral indicators and theoretical simulations, which serve to elucidate alterations in absorption spectra, disparities in binding constants, and structural adaptations. Our study focuses on the theoretical realm, utilizing computational methods and quantum chemistry calculations to explore the electronic structure, energy profiles, and binding energies. This approach allows us to gain a more profound theoretical comprehension of these interactions. This review serves to enhance our comprehension of the complex interactions between zinc and DNA, shedding light on potential applications in drug design, targeted delivery, and DNA-based nanotechnology. It underscores the importance of interdisciplinary collaboration in fully harnessing the diverse capabilities of zinc complexes across multiple domains.
Keywords: Zinc complexes; DNA interaction; In vitro studies; Theoretical modeling; Bioinorganic chemistry